EXPORT MODEL OF MAQOM MUSIC: INTEGRATION OF CULTURE AND ECONOMY - Masharipova Elmira Muxammedsharipovna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores the potential of exporting Maqom music as a model that integrates cultural and economic objectives. It examines how Maqom, as a unique aspect of Uzbekistan’s national heritage, can be promoted globally to generate both cultural influence and economic benefits. The study analyzes strategies for developing sustainable export models through international festivals, digital platforms, collaborations with cultural institutions, and commercial initiatives. Emphasis is placed on balancing authenticity with market-oriented approaches to ensure that Maqom remains a respected cultural product while contributing to the country’s economic development.